2020
DOI: 10.3390/antibiotics9070363
|View full text |Cite
|
Sign up to set email alerts
|

Derivates of the Antifungal Peptide Cm-p5 Inhibit Development of Candida auris Biofilms In Vitro

Abstract: Growth in biofilms as a fascinating and complex microbial lifestyle has become widely accepted as one of the key features of pathogenic microbes, to successfully express their full virulence potential and environmental persistence. This also increases the threat posed by Candida auris, which has a high intrinsic ability to persist on abiotic surfaces including those of surgical instruments and medical tubing. In a previous study, cyclic and helical-stabilized analogues of the antifungal peptide Cm-p5 were desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 26 publications
0
27
0
1
Order By: Relevance
“…Interestingly, in contrary, in the viability assay Pom-1 performed best against C. auris planktonic cells. This finding is a remarkable parallel to derivatives of a peptide from the coastal mollusk Cenchritis muricatus which also failed as antimicrobial peptides against C. auris planktonic cells but efficiently could inhibit biofilm formation [ 37 ]. Nevertheless, the respective semi-inhibitory concentration for biofilm inhibition (IC 50 Biofilm ) of Pom-1 were 4.2 µg/mL for C. auris , 4.6 µg/mL for C. albicans and 3.1 µg/mL for C. parapsilosis ( Figure 3 a).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Interestingly, in contrary, in the viability assay Pom-1 performed best against C. auris planktonic cells. This finding is a remarkable parallel to derivatives of a peptide from the coastal mollusk Cenchritis muricatus which also failed as antimicrobial peptides against C. auris planktonic cells but efficiently could inhibit biofilm formation [ 37 ]. Nevertheless, the respective semi-inhibitory concentration for biofilm inhibition (IC 50 Biofilm ) of Pom-1 were 4.2 µg/mL for C. auris , 4.6 µg/mL for C. albicans and 3.1 µg/mL for C. parapsilosis ( Figure 3 a).…”
Section: Resultsmentioning
confidence: 90%
“…Only moderate activities against planktonic cells has also been described for a set of derivatives a snail derived natural antimicrobial peptide, which turned out to possess remarkable capabilities to inhibit the biofilm formation of C. auris probably based on a yet so far uncharacterized additional activity at very low concentrations of the peptides [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Kubiczek et al (2020) reported that antifungal peptides might have a promising anti-biofilm activity: derivates of the antifungal peptide Cm-p5 exhibited a semi-inhibitory effect at concentrations ranging from 10 to 21 mg/L against C. auris biofilms. In addition, the mature sessile populations were also inhibited by 71–97% [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…To assess the activity of aprepitant/itraconazole against mature biofilms, C. auris cells (at ~1 × 10 5 CFU/ml) were seeded in tissue culture-treated 96-well plates and incubated for 24 h at 35°C to allow for the formation of mature biofilms [ 31–33 ]. Fresh RPMI 1640 media supplemented with aprepitant, itraconazole, or aprepitant/itraconazole, at the same concentrations indicated above, were added to the formed biofilms and incubated for another 24 h at 35°C.…”
Section: Methodsmentioning
confidence: 99%